Beta-Adrenoceptor Antagonists and the Physiological Response to Exercise: Clinical Implications for Training and Rehabilitation - Olejnik, Agnieszka; Zdaniewicz, Mateusz; Adamiak, Jakub; Maciejowski, Michał; Czyżak, Bartłomiej; Baran, Adrian; Jankowska, Justyna; Gronek, Konrad; Huszcza, Beata; Zheng, Edward (Quality in Sport, 2026)
Aim: This narrative review aimed to analyze the impact of beta-adrenoceptor antagonists on the physiological response to exercise and to identify clinical implications for exercise training prescription and exercise-based rehabilitation in patients receiving long-term pharmacotherapy. Material and Methods: A structured literature search was conducted in PubMed, Embase, and the Cochrane Library for studies published between January 2018 and February 2026. Randomized controlled trials, crossover studies, observational research, and relevant systematic reviews evaluating the effects of cardioselective and non-selective beta-adrenoceptor antagonists on peak oxygen uptake (VO₂peak), heart rate response, and ventilatory thresholds in healthy and clinical populations were included. Due to heterogeneity in study design, populations, and pharmacological regimens, findings were synthesized narratively without quantitative meta-analysis. Results: Beta-adrenoceptor antagonists consistently attenuate the chronotropic response to exercise, typically reducing maximal heart rate by approximately 18–19%. Despite this effect, VO₂peak and maximal power output are often preserved through compensatory mechanisms such as increased stroke volume and enhanced arteriovenous oxygen extraction. Under beta-blockade, the relationship between heart rate and external workload becomes blunted, limiting the reliability of heart rate–based methods (e.g., %HRmax, HRR) for exercise intensity prescription. Conclusions: Exercise-based rehabilitation in patients treated with beta-adrenoceptor antagonists requires an individualized, physiology-guided approach. Cardiopulmonary exercise testing with determination of ventilatory thresholds (VT1 and VT2) should be preferred for exercise prescription. In settings without access to CPET, subjective measures such as the Borg Rating of Perceived Exertion scale and the talk test should be incorporated to ensure safety and training effectiveness.